Molecular Characterization of PGC-1β (PPAR Gamma Coactivator 1β) and its Roles in Mitochondrial Biogenesis in Blunt Snout Bream (Megalobrama amblycephala) - Lu, Kangle; Policar, Tomas; Song, Xiaojun; Rahimnejad, Samad (International journal of molecular sciences, 2020)
This study aimed at achieving the molecular characterization of peroxisome proliferator-activated receptor-gamma coactivator 1β (PGC-1β) and exploring its modulatory roles in mitochondria biogenesis in blunt snout bream (Megalobrama amblycephala). A full-length cDNA of PGC-1β was cloned from liver which covered 3110 bp encoding 859 amino acids. The conserved motifs of PGC-1β family proteins were gained by MEME software, and the phylogenetic analyses showed motif loss and rearrangement of PGC-1β in fish. The function of PGC-1β was evaluated through overexpression and knockdown of PGC-1β in primary hepatocytes of blunt snout bream. We observed overexpression of PGC-1β along with enhanced mitochondrial transcription factor A (TFAM) expression and mtDNA copies in hepatocytes, and its knockdown led to slightly reduced NRF1 expression. However, knockdown of PGC-1β did not significantly influence TFAM expression or mtDNA copies. The alterations in mitochondria biogenesis were assessed following high-fat intake, and the results showed that it induces downregulation of PGC-1β. Furthermore, significant decreases in mitochondrial respiratory chain activities and mitochondria biogenesis were observed by high-fat intake. Our findings demonstrated that overexpression of PGC-1β induces the enhancement of TFAM expression and mtDNA amount but not NRF-1. Therefore, it could be concluded that PGC-1β is involved in mitochondrial biogenesis in blunt snout bream but not through PGC-1β/NRF-1 pathway.
Keywords: Liver; biogeneze organel; signální transdukce; DNA-Binding Proteins; játra; Hepatocytes; mitochondrial biogenesis; mitochondrie; fish model; PPARGC1A; Signal Transduction; DNA, Mitochondrial; Transcription Factors; Cyprinidae; Mitochondrial Proteins; transkripční faktory; hepatocyty; PPAR; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; zvířata; mitochondriální DNA; fylogeneze; NRF-1; Organelle Biogenesis; Mitochondria; DNA vazebné proteiny; aminokyseliny; Phylogeny; mitochondriální proteiny; Amino Acids; Animals